Hepatitis C Virus Prevalence in Haemodialysis Patients From Three Centers in Baghdad, Iraq: A Survey By Polymerase Chain Reaction and Serological Methods - Abdullah, Arwa M.; Ahmed, Abdul-Razaq H.; Latif, Ismail I. (Science Journal of University of Zakho, 2014)
Hepatitis C virus infection is a major health problem among haemodialysis patients in developing countries. Nosocomial transmission of HCV infection was a considerable route, particularly during the outbreaks of infection. To compare serological and molecular methods for detection of HCV infection serum samples were screened for anti-HCV antibodies using a fourth generation enzyme-linked immunosorbent assay (ELISA) and positive samples were confirmed by immunoblot assay. All seropositive and seronegative samples were screened for the presence of HCV-RNA by using reverse transcriptase PCR (RT-PCR). The overall prevalence was (41.10%) in the three centers (range: 26.05% to 62.82%) with higher prevalence in Al-Kadhimiya Teaching Hospital. All seropositive samples were tested by reverse transcriptase PCR, and 24/92 (26.09%) of confirmed samples were found to contain HCV-RNA. Additionally, 2/5 (40%) of immunoblot-indeterminate and 1/3 (33.33%) of immunoblot-negative samples were also found to be HCV-RNA positive. Also all seronegative samples were screened for the presence of HCV-RNA by using pooling strategy and 2/136 (1.47%) of anti-HCV negative samples were found to be HCV-RNA positive. Our data emphasize the need for stricter adherence to infection control measures in haemodialysis centers and reinforce the importance of screening by both PCR and serological methods at regular intervals to identify all HCV-infected patients.eng
Keywords: HCV; Haemodialysis; Serological test; RT-PCR